Introducing Management into the Production Function - Mefford, Robert N. (The Review of Economics and Statistics, 1986)
A production function model of industrial plants is developed which incorporates management as a variable. Management is measured by a performance ranking procedure on three commonly used manufacturing criteria. The model also adjusts the capital and labor inputs for quality differences. A nonparametric linear programming test is performed confirming that the data set satisfies consistency, monotonicity, and quasi-concavity conditions of production theory. It is then estimated in three functional forms (translog, CES, and CobbDouglas) for a sample of plants of a multinational, consumer goods manufacturer. Management is shown to be an important input to the production process in these plants regardless of the particular functional form estimated.